The preparation of 1-(β-naphthyl)-3-ferrocenylpyrazole-4-carbaldehyde and syntheses on the base of it - E. Yu. Osipova; A. A. Simenel; A. N. Rodionov; V. V. Kachala; K. Ya. Zherebker (Тонкие химические технологии, 2009)
Synthesis of 1-(β-naphthyl)-3-ferrocenyl pyrazole-4-carbaldehyde was carried out from acetylferrocene and naphthalen-2-ylhydrazine followed by intramolecular cyclization under Vilsmeier-Haack conditions. The reaction of reductive amination of aldehydes obtained with primary and secondary amines including methyl esters of amino acids was studied.